MANAGEMENT OF MILK PRODUCTION ON AN INNOVATIVE BASIS AS A DIRECTION OF DEVELOPMENT OF COMPETITIVE DAIRY CATTLE BREEDING IN AGRICULTURAL ENTERPRISES (INNOVATIVE ECONOMY, 2020)
Parkhomets M.K., Uniiat L.M. MANAGEMENT OF MILK PRODUCTION ON AN INNOVATIVE BASIS AS A DIRECTION OF DEVELOPMENT OF COMPETITIVE DAIRY CATTLE BREEDING IN AGRICULTURAL ENTERPRISESPurpose. The aim of the study is theoretical and methodological substantiation of the principles and the presentation of practical recommendations on the management of the organization of milk production on an innovative basis as a direction of effective development of competitive dairy cattle breeding in agricultural enterprises.Methodology of research. The theoretical and methodological basis were the basic provisions of the economic theory and scientific achievements of scientists, the methods used: retrospective analysis of trends in the economic efficiency of milk production and the dynamics of costs for its production and sales in agricultural enterprises in the region; monographic (showing of the experience of the best enterprises functioning); statistical-economic (study of the influence of internal and external factors on the efficiency of milk production and marketing); abstract-logical (theoretical generalizations and formation of conclusions, literary sources) and others.Findings. The article identifies a clear tendency to increase costs: to use feed for feeding cows; to pay for livestock workers; other direct and general production costs, which caused a significant increase in production and the full cost of milk. The increased growth rates of sales prices of 1 ts of milk as compared to the level of full cost per unit of production have been revealed, which resulted in the increase of the economic efficiency of milk production and sales, and the improvement of financial results of dairy cattle breeding in agricultural enterprises. The influence of the main factors (concentration of livestock, increase of productivity of cows, reduction of the cost of milk, improvement of its qualitative parameters, increase of its sales and increase in the price of milk sales) has been established. It contributes to the increase of the economic efficiency of milk production and its competitiveness.The management of milk production is proposed in the direction of: rational use of available resources; introduction of innovative methods of production and marketing of milk; an expanded reproduction of dairy cattle on an innovative basis that will increase the economic efficiency and competitiveness of the dairy industry, increase rural jobs.Originality. The introduction of management of the organization of milk production on an innovative basis, in contrast to the existing, will contribute to the improvement of economic and economic indicators and the development of competitive dairy cattle breeding in agricultural enterprises.Practical value. The formulated and proposed scientific-methodical and practical developments allow to form a strategy of effective and competitive development of dairy cattle breeding in agricultural enterprises of the region in the conditions of integration of the agro-industrial economy of Ukraine.Key words: production management, innovative methods of production organization, economic efficiency, resource-saving technologies, competitiveness of dairy cattle breeding.
Keywords: Key words; production management; innovative methods of production organization; economic efficiency; resource-saving technologies; competitiveness of dairy cattle breeding.